2007
DOI: 10.3354/dao01841
|View full text |Cite
|
Sign up to set email alerts
|

Screening of freshwater fish species for their susceptibility to a betanodavirus

Abstract: Betanodaviruses, the causative agents of viral nervous necrosis in marine fish, have bipartite positive-sense RNA genomes. Because the genomes are the smallest and simplest among viruses, betanodaviruses have been well studied using a reversed genetics system as model viruses. However, studies of virus-host interactions have progressed slowly because permissive hosts for betanodaviruses (basically larvae and juveniles of marine fish) are only available for limited periods of the year and are not suitable for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 20 publications
1
17
0
2
Order By: Relevance
“…The virus infects a large range of host species—at least 40 species of marine and freshwater fish world-wide [30]—and the known host range continues to expand as new species of fish are used for aquaculture [38,39]. Of further interest is the potential of wild fish to become sub-clinical carriers as virus-contaminated water spreads from aquaculture enterprises into the marine environment particularly for those countries with large mariculture industries [40].…”
Section: Betanodavirusmentioning
confidence: 99%
“…The virus infects a large range of host species—at least 40 species of marine and freshwater fish world-wide [30]—and the known host range continues to expand as new species of fish are used for aquaculture [38,39]. Of further interest is the potential of wild fish to become sub-clinical carriers as virus-contaminated water spreads from aquaculture enterprises into the marine environment particularly for those countries with large mariculture industries [40].…”
Section: Betanodavirusmentioning
confidence: 99%
“…Infections are also reported in freshwater fish, such as Chinese catfish (P. asotus); Australia catfish (Tandanus tandanus); Barramundi (L. calcarifer); Medaka (Oryzias latipes); guppy (Poicelia reticulata) and zebrafish (Danio rerio) [5,22,52,53,62,63,76]. Several experimental infection studies have demonstrated that both marine and fresh water finfish are susceptible to betanodavirus infection [23,38,39,52,53,63]. It has been seen that Asian seabass juveniles are more susceptible to betanodavirus from 10 day onwards with high mortalities of 80 % and smaller sized fish are more prone to the virus than bigger sized fish in the cages.…”
Section: Occurrence and Distributionmentioning
confidence: 99%
“…In addition, our experimental inoculations of striped jack and sevenband grouper with SJNNV or RGNNV revealed that the two viruses have strict host specificity (Iwamoto et al, 2004). Recently, we tested several ornamental fresh water fish for their susceptibility to an RGNNV isolate and showed that the levels of viral susceptibilities were well correlated with the phylogenetic relationships of tested fish (Furusawa et al, 2007). In this study, the viral sequences obtained were better classified by the origi-nated wild fish species rather than by the sampling locations (Table 2).…”
Section: Discussionmentioning
confidence: 98%